ANALISIS SOAL MATERI HIMPUNAN BUKU MATEMATIKA SMP/MTs KELAS VII KURIKULUM 2013 BERDASARKAN TAKSONOMI BLOOM - Sari, Suci Indah; Yensy B, Nurul Astuty; Siagian, Teddy Alfra (JP2MS, 2021)
This research aims to analyse the questions on the middle School Mathematics/MTs class VII Semester I Curriculum 2013 revision 2017 which is reviewed from the aspect of cognitive level accord to Bloom taxonomy revision. This type of research is descriptive research. The Instrument used in this research is a cognitive-level classification sheet of exercises. The data source in this research is the mathematics textbook of Class VII curriculum 2013 revised 2017 compiled by Abdur Rahman As'ari, et al. Curriculum and Conversation Center, Balitbang, Kemendikbud. The results of this research show that based on the cognitive level of the Bloom taxonomy is derived that there are only three categories of cognitive levels on the association's material train question namely remember, understanding, applying. The percentage of cognitive-level categories on the practice of the set material is C1 (remember) 1,25%, C2 (understanding) 41,25%, C3 (applying) 57,5%, C4 (analyze) 0%, C5 (evaluate) 0%, C6 (create) 0%.Keywords: Analysis of Question, Bloom’s Taxonomy, Cognitive Level